New Solutions of Elastic Waves in an Elastic Rod under Finite Deformation. (1st September 2014) - Guo, Peng; Wu, Xiang; Wang, Liangbi
Abstract : The nonlinear wave equation of an elastic rod under finite deformation is solved by the extended mapping method. Abundant new exact traveling wave solutions for this equation are obtained, which contain trigonometric function solutions, solitary wave solutions, Jacobian elliptic function solutions, and Weierstrass elliptic function solutions. The method can be used in further works to establish more entirely new solutions for other kinds of nonlinear evolution equations arising in physics.